The efficacy of nerve growth factor antibody in a mouse model of neuropathic cancer pain - Miyagi, Masayuki (Exp Anim, 2016)
Neuropathic cancer pain is caused by tumors compressing the spinal nerve roots and is usually difficult to treat. The aim of current study was to determine the influence of NGF antibody on pain-related markers and behavior in a mouse model of neuropathic cancer pain. Twenty mice were used to model neuropathic cancer pain by applying murine sarcoma cells to their left sciatic nerve. Ten mice were sham operated. Two weeks after surgery, the murine sarcoma-affected mice were allocated randomly into treatment groups receiving either sterile saline (saline group) or an anti-nerve growth factor antibody (anti-NGF group). Three weeks after surgery (a week after treatment), the pain-related behavior of mice was evaluated using a CatWalk system. Subsequently, bilateral dorsal root ganglia (DRGs) from the L4–L6 levels and spinal cords at L4–L6 levels were resected. DRGs were immunostained for calcitonin gene-related peptide (CGRP) and activating transcription factor 3 (ATF-3), and spinal cords were immunostained for ionized calcium-binding adaptor molecule-1 (iba-1). Mechanical allodynia was observed in mice from the saline group and was improved in mice from the anti-NGF group. CGRP and ATF-3-immunoreactivity in DRGs and microglia expression in the spinal dorsal horn were upregulated in the saline group compared with the sham group, and they were suppressed in the anti-NGF group compared with the saline group (P<0.05). These findings suggest that anti-NGF therapy might be valuable for treating neuropathic cancer pain.